2018
DOI: 10.1590/0037-8682-0367-2017
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis caused by Salmonella enterica serotype Panama in Brazil: first case reported

Abstract: Salmonella infections usually occur as gastroenteritis that is generally self-limited. However, some serotypes of Salmonella can cause severe extra-intestinal infections, such as bacteremia and meningitis. Here, we report the first Salmonella Panama case of meningitis in 4-month-old male newborn in Brazil. The invasive strain isolated was susceptible to all antimicrobial agents tested. The genes agfA, fimA, invA, sfbA, phoP, and slyA were detected using polymerase chain reactions. These findings are relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it is possible that a case of meningitis in an exclusively breastfed 4-month-old patient was contracted from breast milk that was contaminated with an antimicrobial-susceptible S . Panama isolate (41).…”
Section: Transmission Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is possible that a case of meningitis in an exclusively breastfed 4-month-old patient was contracted from breast milk that was contaminated with an antimicrobial-susceptible S . Panama isolate (41).…”
Section: Transmission Vehiclesmentioning
confidence: 99%
“…There are conflicting reports in the literature relating to the AMR status of the S . Panama serovar, with studies in Italy and Brazil reporting low levels of antibiotic resistance (41, 73). They are supported by further reports from Martinique, where 91% of S .…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid complement of the S . Panama serovar has rarely been studied in the past, but it has been reported that S. Panama does not commonly carry the large virulence plasmids that have previously been characterised in other Salmonella serovars 16 . Rather, S. Panama have previously been found to carry a heterogeneous population of plasmids (Table S1) 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent investigations, including CSF culture, revealed gram-negative bacilli that were sensitive to most antibiotics, including ampicillin, ceftriaxone, ceftazidime, chloramphenicol, and trimethoprim. Fortunately, the patient survived [ 11 ]. Another interesting study by Lakew et al described a 13-day-old neonate with Salmonella enterica meningitis; the patient had no remarkable prenatal, natal, or postnatal events.…”
Section: Discussionmentioning
confidence: 99%